Comparative Histological Study of Teat in Jenubi Cow and Her Crossbreed - Karim H. Al-Derawi (Journal of Global Pharma Technology, 2018)
For histological comparative study of the teat, Samples of about 1 cm3 were collected from different parts of teat immediately after slaughter of Jenubi cow and her Friesians crossbreed in Misan government. There are histological similarities in the main structures of the teat found between them. The epithelium of teat canal is thicker in teat of crossbreed cow than the epithelium of teat canal of Jenubi cow. Furstenberg’s Rosette ,is composed of about 10-12 of folds of double layered epithelium in a rose flower like pattern, while in the teat of  crossbreed cow the numbers of the fold decrease to about 7-9 folds .Epithelium thickness of  teat canal is particularly increased for Holsteins Crossbreed cow  compared with Jenubi cow.Keywords: Histology, Teat, Jenubi Cow.